2007
DOI: 10.1111/j.1440-1797.2007.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term intermittent pulse therapy with mizoribine attenuates histologic progression in young patients with severe lupus nephritis: Report of two patients (Brief Communication)

Abstract: Mizoribine (MZR), a novel selective inhibitor of inosine monophosphate dehydrogenase in the de novo pathway, whose mode of action is very similar to that of mycophenolate mofetil, has been successfully applied without serious adverse effects for the treatment of renal diseases. We have previously reported the efficacy and safety of a new MZR treatment regimen, namely, oral MZR intermittent pulse therapy, which we examined based on the observation that it might show superior efficacy to the conventional daily l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Our results suggested that this new treatment protocol may be beneficial and may have a higher efficacy and lower toxicity than the conventional protocol of low-dose (3–4 mg/kg) daily administration of MZR (MZR-C) [9, 10]. Moreover, we recently confirmed that our MZR-P protocol may attenuate histological progression in selected patients with DPLN [11, 12], similar to the results obtained in previously reported pediatric cases receiving long-term iv-CPA [3]. …”
Section: Introductionsupporting
confidence: 65%
“…Our results suggested that this new treatment protocol may be beneficial and may have a higher efficacy and lower toxicity than the conventional protocol of low-dose (3–4 mg/kg) daily administration of MZR (MZR-C) [9, 10]. Moreover, we recently confirmed that our MZR-P protocol may attenuate histological progression in selected patients with DPLN [11, 12], similar to the results obtained in previously reported pediatric cases receiving long-term iv-CPA [3]. …”
Section: Introductionsupporting
confidence: 65%
“…Since the inflamed glomeruli express 14‐3‐3 proteins and heat shock protein 60, which are known to be MZR‐binding proteins, MZR may directly interact with inflamed glomerular cells, because MZR is directly excreted unchanged into the urine . Clinically, we previously reported that post‐treatment renal biopsy specimen from patients with proliferative lupus nephritis treated with MZR, showed marked attenuation of glomerular and interstitial lesions, and significantly reduced the number of infiltrated macropharges . Ikezumi et al .…”
Section: Discussionmentioning
confidence: 90%
“…1 Clinically, MZR has been successfully used without any serious adverse effects for the long-term treatment of young patients with lupus nephritis. [1][2][3] Besides its immunosuppressive effects, MZR has recently been reported to suppress the progression of histologic chronicity in selected patients with lupus nephritis and immunoglobulin A (IgA) nephropathy. [1][2][3][4] Moreover, some experimental reports described that MZR attenuates tubulointerstitial fibrosis in rat models of unilateral ureteral obstruction, non-insulindependent diabetes and peritoneal fibrosis via suppression of macrophage infiltration of the interstitium.…”
Section: Conclusion: Mizoribine Itself Selectively Attenuated the Expmentioning
confidence: 99%
See 1 more Smart Citation
“…[113] Mizoribine has been developed in Japan and has been shown to be a potent immunosuppressant in children with relapsing corticosteroid-dependent nephritic syndrome. [115][116][117] Side effects have been reported as a mild transient hyperuricemia. [114] There has also been a case report of its successful use in JRA, childhood renal sarcoidosis, and young patients with lupus nephritis.…”
Section: Mizoribinementioning
confidence: 99%